Drawing on local knowledge and attitudes for the conservation of critically endangered rhino rays in Goa, India - Gupta, T; Milner-Gulland, EJ; Dias, A; Karnad, D (Wiley, 2023)
In the context of marine species declines in data-limited regions, local ecological knowledge (LEK) is a valuable source of information on species ecology and historical trends. LEK can also help understand how threatened species exist within a local culture, in terms of their uses and values, and reveal attitudes towards their conservation. Rhino rays (guitarfish and wedgefish) are highly threatened by overfishing with most species critically endangered, yet poorly studied in countries like India that fish them the most. We drew on LEK to understand the socio-ecological status of rhino rays in Goa, on the west coast of India. We investigated their habitat use and seasonality, interaction with fisheries, socio-economic uses and relational values. We also explored attitudes of fishers towards rhino rays and their conservation. A combination of semistructured interviews and key informant interviews (88 in total) was conducted with fishers at multiple sites. Local knowledge suggests that nearshore habitats around river mouths form important nursery grounds for some rhino rays, and provided insights on their seasonality and breeding. Rhino rays appeared to be targeted historically but are entirely bycaught at present, with highest catches in gillnets and in the South Goa district, during September and October. LEK indicated that taxa like sawfish (Pristis spp.) and wedgefish (Rhynchobatus spp.) have severely declined or disappeared from this region. We coded different relational values, from recreation (rhino rays are consumed and enjoyed with alcohol) to symbolic values (rhino rays are considered lucky). All key informants expressed positive attitudes towards rhino ray conservation and stated that a ban on landing these species would have little to no impact on fisher earnings. The usefulness of LEK suggests it should be brought into the scientific mainstream to support development of more equitable and socially appropriate management plans. Fostering relational values can reinforce fishers' positive attitudes, thereby enhancing rhino ray conservation. Their low commercial value and potentially high post-capture survival suggest that using norm-based approaches to promote live release may be successful. Further research on rhino ray ecology and human dimensions can support the development of appropriate conservation interventions.